Westminster, city for all. A multi-scalar approach for a healthy community - Piera Pellegrino (Agathón)
In the last few years, the interest in the relationship between urban planning and the topic of citizens’ health has spread supported by the action of the World Health Organization which has focused attention on the ‘determinants’ of health, understood as socio-economic, cultural and environmental conditions, as well as life and work. Starting from the assumption that urban planning plays a decisive role in promoting healthy lifestyles, this contribution examines the case of the City of Westminster, to highlight the integration of the health topic in urban planning tools. To be effective, policies for improving health and wellbeing require a multi-scalar approach, among strategies, including sectorial ones, plans and projects, and a multidisciplinary interaction between the actors, to allow the definition of shared actions of development.